(3JGL GdeYGQa hJGQjN GdNdGFas - (3eMeO Hf eMehO Hf CHi GdSYGOGJ Hf eMeO Hf GdYHGS Hf eMeO CHi GdLhO GdSdehfi dGTGaYis; (3Gdecjf , LQLS Hf GdYejO Hf GdjGS GdeYQha HGdecjf, GdTjN Gdecjf, GHf GdYejO,J (B672 (3g` s
(3ChdgG (B:s
(3Gddge dGSgd EdG eG LYdJg SgdkG s
(3VefI JGQjNkG deUQ ef BOe Ydjg GdSdGe Edi eOI Gdedc GdGTQa bGjJHGi GdeMehOis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B55 s
Keywords: (3GdJGQjNs